Investigating the Induction of Vaccine-Induced Th17 and Regulatory T Cells in Healthy, Mycobacterium bovis BCG-Immunized Adults Vaccinated with a New Tuberculosis Vaccine, MVA85A - de Cassan, Simone C. (American Society for Microbiology (ASM), 2010)
Tuberculosis (TB) remains a threat to global health. While advances in diagnostics and treatment are crucial to the containment of the epidemic, it is likely that elimination of the disease can only be achieved through vaccination. Vaccine-induced protection from Mycobacterium tuberculosis is dependent, at least in part, on a robust Th1 response, yet little is known of the ability of TB vaccines to induce other T-cell subsets which may influence vaccine efficacy. Interleukin-17A (IL-17A) is a proinflammatory cytokine produced by Th17 cells which has been associated with both immune pathology and protection against infectious disease. Following vaccination with MVA85A, a viral vector vaccine aimed at enhancing immune responses to M. tuberculosis, antigen-specific IL-17A-producing T cells were induced in the peripheral blood of healthy volunteers. These T cells are detected later than gamma interferon (IFN-γ)-secreting T cells and are of a low magnitude. Preexisting immune responses to mycobacterial antigens were associated with higher CD4(+) CD25(hi) CD39(+) T-cell levels in the periphery and a reduced capacity to produce IL-17A following immunization. These data highlight the intricate balance of effector and regulatory immune responses induced by vaccination and that preexisting immunity to mycobacterial antigens may affect the composition of vaccine-induced T-cell subsets.